APLIKASI KOMPOS TITONIA DAN JERAMI TERHADAP PENGURANGAN INPUT PUPUK BUATAN DAN PENGARUHNYA TERHADAP PRODUKSI PADI - Gusnidar Gusnidar; Syafrimen Yasin; Burbey Burbey; Resi Ezrari (Jurnal Solum, 2011)
A research about “Application of Tithonia and rice straw compost on reduction of commercial fertilizer application and it effects on rice production” has been conducted in Sicincin, 2x11 Enam Lingkung, Padang Pariaman Region as well as in Soil Laboratory Agriculture Faculty, Andalas University, Padang.  This research was conducted from January until May 2009.  The objective of this research was to evaluate effect of titonia and rice straw compost application at intensification rice field on rice production and reduction of commercial fertilizer use.  A field research was allocated based on Randomized Block Design with 6 treatments, those were: A= Farmer Tradition Input (200 kg Urea ha-1+ 200 kg SP-36 ha-1);B=Recomended Input (R= 200 kg Urea ha-1+ 100 kg SP-36 ha-1+ 75 kg KCl ha-1); C= Application of Compost (5  ton rice straw ha-1) +  100% Recommendation Input (Urea + KCl + SP-36); D= Application of Compost (5 ton rice straw ha-1) +  Urea 200 kg ha-1,without KCl + P-starter 10 kg SP-36 ha-1; E= Application of Compost (Titonia 2,5 ton ha-1 + rice straw 2,5 ton ha-1) + Urea 75 % (R) (150 kg ha-1), withou KCl, and P-starter 10 kg SP-36 ha-1; F= Application of Compost (Titonia 2,5 ton ha-1 + 2,5 rice straw ton ha-1) + Urea 50 % (R) (100 kg ha-1), without KCl,and P-starter 10 kg SP-36 ha-1. Data from field research were statistically analysed.  If the F-calculated was significantly different, they would be further analysed using LSD (5%).  The results showed that application of  rice straw-titonia mix compost on intensification rice field could reduce commercial fertilizer by 50 kg Urea ha-1 (=25% Recommendation), and 75 kg KCl ha-1and 100 kg SP-36 ha-1 (100% recommendation) with increasing yield by 1.1 ton ha-1 Harvested Dry Yield (GKP) and 1.03 t/ha Mill Dry Yield (GKG).  If it was compared to fertilization based on farmer tradition, application of  rice straw-titonia mix compost on intensification rice field could reduce commercial fertilizer by 50 kg Urea ha-1 (25% R), and 190 kg SP-36 ha-1 (95% ).Keywords: compost, fertilizers, intensification,  rice  straw, titonia.